The complete chloroplast genome and phylogenetic analysis of Syringa reticulata subsp. amurensis (Rupr.) P.S.Green & M.C.Chang from Qinghai Province, China. Issue 7 (3rd July 2021) - Wang, Jiuli; Tian, Tian; Han, Xia; Ye, Bin; Ma, Xiuling; Meng, Xianwen; Xie, Jiuxiang; Zhou, Huakun
Abstract: Syringa reticulata subsp. amurensis (Rupr.) P. S. Green & M. C. Chang (Oleaceae) is a shrub or tree with high medicinal value as well as great ecological significance as an urban garden plant. To better understand the molecular genetics and evolutionary of S. reticulata subsp. amurensis, its complete chloroplast genome was sequenced and annotated. The assembled chloroplast genome is a circular 156, 141 bp sequence, consisting of 87, 108 bp large single copy (LSC) region and 17, 239 bp small single copy (SSC) region, which were flanked by a pair of 25, 897 bp inverted repeats (IRs). The GC content of the chloroplast genome is 36.14%. Moreover, a total of 132 functional genes were annotated, including 88 protein-coding, 36 tRNA, and eight rRNA genes. Phylogenetic analysis showed that S. reticulata subsp. amurensis was most closely related to S. reticulata subsp. Pekinensis and the genus Syringa is paraphyletic group. This study provides important information for further phylogenetic studies on S. reticulata subsp. amurensis and its allies.